Harmonisasi SAK dan Aturan Pajak: Mungkinkah? - Sukendar, Heri Sukendar (Binus Business Review, 2014)
This paper is intended to illustrate the fact that the case today, especially in Indonesias commitment to convergency of IFRS, where the decision was certainly not out of global importance that in order to improve the information from the financial statements of companies in Indonesia. In addition, the IFRS Convergence is one of the Indonesian government agreements as a member of the G20 forum, the results of the meeting of G20 leaders in Washington DC forum, 15 November 2008. On the other hand, the tax rules that apply are still using the old accounting standards and do not follow the development of increasingly different. Previous differences between GAAP and tax rules are limited to the "deductible and non-deductible" which is resolved through fiscal reconciliation mechanism with positive correction and correction negatipnya. The widening gap today would be a separate issue for IAI as the organization of the accounting profession. Tax Accountant compartment formation in March 2014 is a serious evidence of the organization as an anticipation, particularly in an effort to bridge the gap widening